Organelle stresses and energetic metabolisms promote endothelial–to–mesenchymal transition and fibrosis via upregulating FOSB and MEOX1 in Alzheimer’s disease - Saaoud, Fatma; Ben Issa, Mohammed; Liu, Lu; Xu, Keman; Lu, Yifan; Shao, Ying; Han, Baosheng; Jiang, Xiaohua; Liu, Xiaolei; Gillespie, Avrum; Luo, Jin Jun; Martinez, Laisel; et al. (Frontiers in Molecular Neuroscience, 2025)
IntroductionEndothelial-to-mesenchymal transition (EndoMT), cell death, and fibrosis are increasingly recognized as contributing factors to Alzheimer’s disease (AD) pathology, but the underlying transcriptomic mechanisms remain poorly defined. This study aims to elucidate transcriptomic changes associated with EndoMT, diverse cell death pathways, and fibrosis in AD using the 3xTg-AD mouse model.MethodsUsing RNA-seq data and knowledge-based transcriptomic analysis on brain tissues from the 3xTg-AD mouse model of AD. This included pathway-level analysis of gene expression changes across multiple brain cell types. Mechanistic insights were further validated using single-cell RNA sequencing (scRNA-Seq) dataset from human AD brain.ResultsOur analysis showed that in the 3xTg-AD model: (i) multiple brain cell type genes are altered, promoting EndoMT through upregulation of RGCC and VCAN; (ii) genes related to various types of cell death, including apoptosis, ferroptosis, necrosis, anoikis, mitochondrial outer membrane permeability programmed cell death, mitochondrial permeability transition-driven necrosis, NETotic, and mitotic cell death, are upregulated in the several brain cell types; (iii) fibrosis-related genes are upregulated across multiple brain cell types. Further mechanistic analysis revealed: (1) mitochondrial stress through upregulation of mitochondrial genes in the brain cells; (2) upregulation of cellular, oxidative, and endoplasmic reticulum (ER) stress genes; (3) nuclear stress via upregulation of nuclear genes, transcription factors (TFs), and differentiation TFs FOSB and MEOX1; (4) metabolic reprogramming/stress through the upregulation of genes related to lipid and lipoprotein metabolism, fatty acid oxidation (FAO), glucose metabolism, and oxidative phosphorylation (OXPHOS); (5) catabolic stress via upregulation of catabolic genes. Single-cell RNA-Seq data indicated that many of these were also increased in AD patients’ brain cells. These changes were reversed by knockdown of the ER stress kinase PERK (EIF2AK3) and deficiencies in FOSB and MEOX1.DiscussionThis study uncovers previously unrecognized molecular signatures of organelle stress and bioenergetic reprogramming that drive EndoMT, cell death, and fibrosis in AD. The reversal of these changes via PERK, FOSB, and MEOX1 inhibition highlights potential therapeutic targets for mitigating neurodegenerative processes in AD.